Transformation Of The EU Law Related To The Etabilishment Of National Law In The England In The Law Perspective Of International Organizations - Syaravina Lubis (Journal of Law Science, 2022)
The economic upheaval of a country is one of the reasons for the formation of an international organization, namely the European Union. The goal of the European Union itself is to promote through the community the harmonious, sustainable development of economic activity, steady improvement, rapid improvement of living standards, quality of life and closer relations between member states. This research has a problem formulation consisting of the transformation of EU law into law in the member states of the European Union, the transformation of EU law in the UK, and a challenge as a legal effort related to the transformation of EU law in the UK according to International Organization Law. This study uses a normative juridical research method. The results of the research on the transformation of European Union Law into National Law of member countries, namely by establishing Regulations, Directives, Decisions that must be applied in member countries. EU law has the supremacy of overriding the National Laws of member states. The transformation of European Union Law in the UK began with the agreement of the European Communities Act 1972 which was the UK's ratification of EU Law. Challenge as a legal remedy related to the transformation of European Union Law in the UK is permitted under Articles 230 and 232 of the European Union Agreement, namely by submitting a complaint to the national court in accordance with the time specified to carry out the challenge, this challenge action can end with an amendment. The conclusion of the research is the transformation of European Union Law in member countries in the form of Regulations, Directives, and Decisions. The European Union Law Transformation in the UK is regulated through the European Communities Act 1972. Challenge as a legal remedy related to the transformation of EU Law in the UK is allowed in order to create a good implementation. Suggestions related to research is that it is better to ensure that the transformation of European Union Law has been implemented as intended. The transformation of EU Law in the UK should ensure that UK National Law can be waived in the event of a conflict with EU Law which is immediately effective. Conduct in-depth negotiations, ask for opinions from representatives of each member country so that unity is achieved to facilitate the implementation of European Union Law in member countries and minimize challenges to European Union Law.